Functional Mapping of Adhesiveness on Live Cells Reveals How Guidance Phenotypes Can Emerge From Complex Spatiotemporal Integrin Regulation - Robert, Philippe; Biarnes-Pelicot, Martine; Garcia-Seyda, Nicolas; Hatoum, Petra; Touchard, Dominique; Brustlein, Sophie; Nicolas, Philippe; Malissen, Bernard; Valignat, Marie-Pierre; Theodoly, Olivier (Frontiers in Bioengineering and Biotechnology, 2021)
Immune cells have the ubiquitous capability to migrate disregarding the adhesion properties of the environment, which requires a versatile adaptation of their adhesiveness mediated by integrins, a family of specialized adhesion proteins. Each subtype of integrins has several ligands and several affinities states controlled by internal and external stimuli. Crawling cells expressing several integrins and exposed to various types and densities of ligands form a complex system favorable to the emergence of sophisticated phenotypes at cell scale. However, probing cell adhesion properties on live cells without perturbing cell motility is highly challenging, especially in vivo. Here, we developed a novel in vitro method using micron size beads pulled by flow to probe functionally the local surface adhesiveness of live motile cells. This method allowed a functional mapping of the adhesiveness mediated by VLA-4 and LFA-1 integrins on the trailing and leading edges of live human T lymphocytes. We show that processes of cell polarization enhance integrin-mediated adhesiveness towards cell rear for VLA-4 and cell front for LFA-1. Sharpin, an LFA-1 inhibitor in lymphocyte uropod, was found here to decrease adhesiveness in rear and front cell, whereas Myosin II had no detectable effect. Inhibiting crosstalk of LFA-1 towards VLA-4 and activating crosstalk of VLA-4 toward LFA-1 were modulating cell adhesiveness with long distance effect across the cell. Quantitative 3D immuno-imaging yielded densities of high affinity LFA-1 and VLA-4 around respectively 50 and 100 molecules/µm2 in basal adhesion zone, and a latent adhesiveness of dorsal zones was not grasped by high affinity integrin immunostaining but assessed by functional assays. Altogether, combination of molecular and live functional assays was instrumental to decipher further the spatiotemporal regulation of integrin-mediated adhesiveness at molecular and cell scale, and to explain the emergence of complex phenotypes such as the bistable orientation of lymphocytes downstream or upstream in a flow.